From MRI to FEM: an automated pipeline for biomechanical simulations of vertebrae and intervertebral discs - Nispel, Kati; Lerchl, Tanja; Gruber, Gabriel; Moeller, Hendrik; Graf, Robert; Senner, Veit; Kirschke, Jan S. (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction Biomechanical simulations can enhance our understanding of spinal disorders.Applied to large cohorts, they can reveal complex mechanisms beyond conventional imaging.Therefore, automating the patient-specific modeling process is essential.We developed an automated and robust pipeline that generates and simulates biofidelic vertebrae and intervertebral disc finite element method (FEM) models based on automated magnetic resonance imaging (MRI) segmentations. In a first step, anatomicallyconstrained smoothing approaches were implemented to ensure seamless contact surfaces between vertebrae and discs with shared nodes. Subsequently, surface meshes were filled isotropically with tetrahedral elements. Lastly, simulations were executed. The performance of our pipeline was evaluated using a set of 30 patients from an in-house dataset that comprised an overall of 637 vertebrae and 600 intervertebral discs. We rated mesh quality metrics and processing times.With an average number of 21 vertebrae and 20 IVDs per subject, the average processing time was 4.4 min for a vertebra and 31 s for an IVD. The average percentage of poor quality elements stayed below 2 % in all generated FEM models, measured by their aspect ratio.Ten vertebra and seven IVD FE simulations failed to converge.The main goal of our work was to automate the modeling and FEM simulation of both patient-specific vertebrae and intervertebral discs with shared-node surfaces directly from MRI segmentations. The biofidelity, robustness and time-efficacy of our pipeline marks an important step towards investigating large patient cohorts for statistically relevant, biomechanical insight.